A high temperature resistant neodymium iron boron magnet and its preparation method
By preparing neodymium iron boron magnets containing main phase magnetic powder, auxiliary alloy powder and filled phase magnetic powder, and using multi-stage pressing and sintering tempering technology, the problem of high-temperature neodymium iron boron magnet failure in offshore or offshore operation motors is solved, and good thermal stability and composite corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411496005.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Existing high-temperature resistant neodymium iron boron magnets are prone to failure in motors operating at sea or offshore, showing weak heat resistance and irreversible magnetic properties, and it is difficult to effectively solve the problem of composite corrosion.
By preparing a neodymium iron boron magnet containing main phase magnetic powder, auxiliary alloy powder and filled phase magnetic powder, a multi-stage pressing and sintering tempering process is adopted to ensure that the magnet has good thermal stability and anti-grain boundary corrosion in high temperature and high humidity environments.
The long-term good thermal stability and composite corrosion resistance of neodymium iron boron magnets in high temperature and high humidity environments are achieved, ensuring the stability and durability of magnetic properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnet material manufacturing, and in particular relates to a high-temperature resistant neodymium iron boron magnet and a preparation method thereof. Background Art
[0002] As a new generation of rare earth permanent magnet materials, NdFeB magnets are widely used in various types of machinery and equipment, such as magnetic bearings, sensors, filtration systems, motors, power stations, etc. However, during use, technicians found that the NdFeB magnets used in ship motors and offshore wind power stations are prone to failure. The heat generated by the operation of the motor causes the magnet to oxidize, resulting in obvious thermal corrosion, showing weak heat resistance that is obviously not in line with expectations, and irreversible magnetic properties decrease due to oxidation in a relatively high temperature environment. Moreover, even if technicians in this field use high-temperature resistant special NdFeB magnets to adapt to relatively high temperature and high humidity working environments, they cannot avoid magnet failure. The high-temperature resistant NdFeB magnets they show also show weak heat resistance after a period of use, and their residual magnetism temperature coefficient is significantly reduced, far less than expected.
[0003] Different from conventional thermal corrosion, in most studies, many technicians believe that the main form of corrosion damage of offshore and near-shore motors used in ships and wind power stations is salt spray corrosion, because it has the characteristics of electrochemical corrosion. The air in the above-mentioned operating environment also contains more chlorine and higher humidity, which meets the conditions of salt spray corrosion and is easy to cause salt spray corrosion. In this regard, the current technical focus is on improving the salt spray corrosion resistance of high-temperature resistant NdFeB magnets, but it has always been difficult to effectively solve the problem that the remanence temperature coefficient of high-temperature resistant NdFeB magnets used in offshore motors is too low and the actual heat resistance performance is far below expectations.
[0004] In the technical research, technicians discovered a composite corrosion effect that is different from the traditional concept. This composite corrosion effect has the characteristics of thermal corrosion and electrochemical corrosion at the same time, but it is different from the salt spray corrosion and electrochemical corrosion. Therefore, it is necessary to further study and propose newer solutions for this composite corrosion mechanism. Summary of the invention
[0005] In order to solve the currently difficult and inevitable problems of high-temperature resistant NdFeB magnets used in offshore or ocean areas, such as unknown performance degradation that is prone to occur due to different corrosion forms, the prior art research has not deeply understood that such high-temperature resistant NdFeB magnets are prone to targeted solutions, the present invention provides a high-temperature resistant NdFeB magnet, and a method for preparing the NdFeB magnet.
[0006] The main purpose of the present invention is:
[0007] 1. Ensure that the NdFeB magnet has good magnetic properties;
[0008] 2. Ensure that the NdFeB magnet has good thermal stability;
[0009] 3. Targetedly strengthen the ability of NdFeB magnets to cope with complex corrosion so that they can be used in offshore or near-shore motors.
[0010] To achieve the above objectives, the present invention adopts the following technical solutions.
[0011] A method for preparing a high temperature resistant neodymium iron boron magnet.
[0012] The method comprises:
[0013] 1) respectively preparing main phase magnetic powder, auxiliary alloy powder and filling phase magnetic powder, mixing them evenly to obtain mixed magnetic powder, evenly filling the mixed magnetic powder in a mold, orienting and pressing to obtain a magnet blank;
[0014] 2) The magnet blank is sintered, the surface is cleaned and then tempered to obtain a high temperature resistant NdFeB magnet.
[0015] As a preference,
[0016] Step 1) The main phase magnetic powder is composed of:
[0017] Nd 27.0~28.0 wt%, B 1.0~1.2 wt%, the balance is Fe;
[0018] Step 1) The auxiliary alloy powder is composed of:
[0019] Fe 25.0~27.0 at%, NdCu 11.0~18.0 at%, the balance is Cu;
[0020] Unless otherwise specified, the atomic ratio of Nd to Cu in the NdCu raw material (i.e., NdCu alloy) used in the present invention is 2:8;
[0021] Step 1) The filling phase magnetic powder is composed of:
[0022] Nd 13.8~14.5 at%, Fe 5.5~6.5 at%, the balance is B.
[0023] As a preference,
[0024] Step 1) The main phase magnetic powder is respectively made of neodymium, boron and iron according to the composition, mixed evenly, smelted in an inert gas and then crushed to 400-500 mesh to obtain the main phase magnetic powder;
[0025] Step 1) The auxiliary alloy powder is respectively made of iron, neodymium copper alloy and copper, and mixed evenly, smelted in an inert gas, and then crushed into auxiliary alloy powder of 100-200 mesh;
[0026] Step 1) The filling phase magnetic powder is prepared by mixing neodymium, boron and iron according to the composition, smelting them in an inert gas and then crushing them into 1000-1200 meshes to obtain the filling phase magnetic powder.
[0027] As a preference,
[0028] In step 1), the mass ratio of the main phase magnetic powder, the auxiliary alloy powder and the filling phase magnetic powder is 1: (0.03-0.08): (0.04-0.06).
[0029] As a preference,
[0030] In step 1), the orientation magnetic field intensity is controlled to be 1.5 to 1.7 T, the orientation time is 25 to 35 min, and a pressing pressure of 4 to 6 MPa is applied during the orientation process.
[0031] As a preference,
[0032] Step 1) The pressing is performed in stages, and the staged pressing includes a first stage pressing procedure, a second stage pressing procedure and a third stage pressing procedure in sequence, and all the pressing procedures are in the form of isostatic pressing;
[0033] The first-stage pressing procedure controls the pressing temperature to be 80-100°C, the pressing pressure to be 220-250 MPa, and the pressing time to be 15-25 min;
[0034] The two-stage pressing program controls the pressing temperature to be 510-530°C, the pressing pressure to be 60-80 MPa, and the pressing time to be 30-60 s;
[0035] The three-stage pressing program controls the pressing temperature to be 70-110° C., the pressing pressure to be 120-130 MPa, and the pressing time to be 10-20 min.
[0036] As a preference,
[0037] Step 2) The sintering is carried out in a protective atmosphere, the sintering temperature is 1050-1080°C, and the sintering time is 3-4 hours.
[0038] As a preference,
[0039] Step 2) the tempering is staged tempering;
[0040] The staged tempering includes, in sequence, maintaining the temperature at 550-650°C for 2.0-2.5 h, and maintaining the temperature at 400-500°C for 4.5-5.0 h.
[0041] A high temperature resistant NdFeB magnet which can effectively resist the composite corrosion phenomenon consisting of grain boundary corrosion and thermal corrosion and exhibits good high temperature resistance.
[0042] In the technical research of the present invention, technicians have discovered a composite corrosion mechanism that is different from the traditional concept. This composite corrosion mechanism has the characteristics of thermal corrosion and electrochemical corrosion at the same time, but it is different from the electrochemical corrosion form of salt spray corrosion. The composite corrosion mechanism discovered by technicians mainly includes two types: grain boundary corrosion and thermal corrosion. Among them, grain boundary corrosion is usually relatively slow, and the degree of harm caused under normal circumstances is far less than that of salt spray corrosion. In most cases, grain boundary corrosion will be masked by other corrosion phenomena. Therefore, it is a relatively special and usually difficult to pay attention to corrosion mechanism. Moreover, as a kind of electrochemical corrosion, grain boundary corrosion is closer to salt spray corrosion, but the two are essentially different. Salt spray corrosion usually occurs in a marine atmospheric environment with high temperature, high humidity and high salt spray, such as Wanning, Xisha and Qingdao, and it is especially frequent in the area with a height of 0.4 to 1.6 m near the sea surface. With the increase in altitude, the salt spray corrosion effect in the altitude range of 10 to 100 m should conform to the characteristics of the inverse "S" distribution of chloride ions in the marine and offshore atmosphere. However, the motors of some wind power stations happen to be located in the valley area of chloride ion concentration at about 30 m, but obvious electrochemical corrosion has occurred. Based on this, the technicians discovered that the corrosion of NdFeB in wind power station electrodes is similar to that of NdFeB in marine ship motors, and even the corrosion of NdFeB magnets in inland dam motors has some performance trends that are quite similar. Only then did they conduct in-depth research and discover a new composite corrosion mechanism. During the salt spray corrosion process, salt (especially chloride) is adsorbed on the surface of the magnet, reducing the surface resistance. At the same time, chloride ions penetrate the oxide layer and protective layer on the surface of the NdFeB magnet and react with the internal metal to form a "micro-battery" to cause electrochemical reaction and metal corrosion. Under the action of the "micro-battery", the material corrosion is intensified, causing corrosion pits to form on the surface of the magnet until the inside of the material is exposed to the corrosive environment, resulting in a decrease in the mechanical strength of the magnet. This type of corrosion usually mainly destroys the surface structure of the NdFeB magnet, and is particularly prone to degradation of the protective layer of the NdFeB magnet, but usually has little effect on its heat resistance.
[0043] Different from conventional salt spray corrosion, the grain boundary region usually has different chemical composition and crystal structure, and the corrosion is caused by the difference in electrochemical properties at the grain boundary. Therefore, the grain boundary becomes the preferred corrosion path, and a corrosion channel is formed along the grain boundary, which leads to the weakening of the bonding force between the grains. For example, the Nd-rich phase and the B-rich phase at the grain boundary will be corroded first. This corrosion has the characteristics of "small anode-large cathode", which leads to the degradation of magnet performance. Grain boundary corrosion can also cause stress concentration and impurity segregation near the grain boundary, which obviously has a destructive effect on the internal structure of the magnet and will significantly affect the heat resistance of the NdFeB magnet. Therefore, in a high temperature and high humidity environment, grain boundary corrosion leads to a rapid decline in the heat resistance of the high temperature resistant NdFeB magnet, resulting in a decrease in its residual magnetism temperature coefficient, so that it no longer has good high temperature resistance.
[0044] It can be seen that salt spray corrosion and grain boundary corrosion have different effects on the heat resistance of NdFeB magnets. Usually, because salt spray corrosion mainly affects the protective layer on the surface of the magnet and mainly occurs in the early stage, salt spray corrosion has little effect on the heat resistance of NdFeB. Grain boundary corrosion is more in-depth, resulting in severe internal structural damage such as grain boundary fracture and magnet pulverization, which has a greater impact on the heat resistance of NdFeB. However, grain boundary corrosion is usually not easy to occur because its process is relatively slow, but the heat generated by the motor promotes this process, resulting in the composite corrosion mechanism of grain boundary corrosion-thermal corrosion. The actual development process is far beyond expectations. If the NdFeB magnet is completely exposed to high temperature and high humidity conditions, it will even produce very serious corrosion in about 15 days.
[0045] This is because in the marine atmosphere, high temperature accelerates the diffusion of ions (such as hydroxide ions and chloride ions) near the grain boundaries, accelerates impurity segregation, and causes grain boundary migration or phase change, exposing new grain boundaries that are more sensitive to corrosion. With the acceleration of oxidation, grain boundaries are more susceptible to grain boundary corrosion. The main phase grains caused by grain boundary corrosion fall off and aggravate the degree of thermal corrosion. After a period of time, thermal corrosion significantly increases the electrochemical potential of the grain boundaries, further aggravating the degree of thermal corrosion. In the marine atmosphere, water molecules further wet the grains, providing a driving force for the magnet to adsorb ions and ions (from salt decomposition, water electrolysis, oxygen reduction, etc.) to aggregate, the conductivity of the magnet surface increases, and the oxide layer formed promotes corrosion. It can be seen that a relatively high temperature and high humidity working environment is prone to mutual promotion and aggravation of grain boundary corrosion and thermal corrosion. In the later stage, it may even be accompanied by salt spray electrochemical corrosion, causing the main phase grains of high temperature resistant NdFeB magnets to fall off, aggravating the damage to the magnet. Therefore, under the composite corrosion mechanism, it is difficult for the magnet to maintain excellent magnetic properties, causing the high-temperature resistant NdFeB magnet, which could originally withstand temperatures above 150°C and maintain good magnetic properties, to experience a significant performance degradation in the operating temperature range of 90 to 120°C.
[0046] Based on this, the present invention aims at a new corrosion mechanism and effectively optimizes the performance of NdFeB magnets. It is generally believed in the art that low melting point grain boundaries have a positive effect on the magnetic texture of magnets, and heavy rare earth elements Dy and Tb are often added to improve the anisotropy of magnets, thereby improving the coercive force of magnets. However, heavy rare earth elements usually refine the grains to nanometer level, especially in an environment with high temperature and air water content exceeding 70%, the magnet pores are easily combined with O atoms, and the main phase generates neodymium oxide, iron oxide, etc., which aggravates the corrosion trend. The amorphous phase with high Fe content is suppressed by high temperature due to the demagnetization coupling effect, and it is easy to form a reverse magnetization nucleation point, thereby causing the magnetic properties of the magnet to be significantly reduced. At the same time, the art often strengthens the heat resistance and salt spray resistance of magnets by heavy rare earth elements. However, because the above-mentioned marine atmospheric environment corrodes magnets in a complex manner, the actual corrosion mechanism is different from the previous cognition, and heavy rare earth elements are easily gathered at grain boundaries and defects, which are easy to increase the grain boundary corrosion trend here, and interact with thermal corrosion to promote the composite corrosion process, thereby causing the magnet to be unstable. Therefore, for the newly discovered composite corrosion mechanism of intergranular corrosion and thermal corrosion, other rare earth elements should be avoided when strengthening the magnet.
[0047] However, when the main phase components are directly sintered, there is almost no intergranular phase in the magnet, the grains are mechanically bonded, and a short-range ferromagnetic coupling effect is generated, which significantly reduces the coercive force of the magnet. In order to improve the magnetic properties, heat resistance, and salt spray resistance of the magnet, the present invention provides a method for preparing a high-temperature corrosion-resistant NdFeB magnet, and regulates the magnet composition and structure under the premise of completely avoiding heavy rare earths.
[0048] The present invention improves the bonding force between crystal grains and the coercive force of the magnet by appropriately adding auxiliary alloy powder. The NdCu component can ensure that the magnet forms a liquid phase during the sintering process to further play a role in wetting and linking to wet the crystal grains, while the atomic diffusion rate is increased to promote uniform distribution of components. The auxiliary alloy provides a higher content of solid-liquid sintering environment during sintering. Most importantly, the present invention slows down the electrochemical corrosion of the grain boundary phase and the main phase by accurately using the auxiliary alloy NdFeCu, because the introduction of Cu in the form of NdFeCu alloy on the basis of ensuring compatibility can promote the formation of a thin layer of continuous grain boundary phase, reduce the electrode potential difference between the grain boundary phase and the main phase, and reduce the tendency of electrochemical corrosion of the magnet.
[0049] During the sintering and tempering process, the Cu-containing components segregate on the grain boundaries adjacent to the main phase, and the low-melting-point alloy forms a neodymium-rich liquid phase. The neodymium-rich liquid phase penetrates into the main phase grains through capillary action, and is continuously and evenly distributed inside the magnet, forming a homogenized Nd-rich phase and greatly refining it, reducing the number of large Nd-rich phases, narrowing the corrosive medium channel, and slowing down the corrosion rate in a kinetic sense.
[0050] However, using too much auxiliary alloy will increase the intergranular corrosion and increase the size of the intergranular corrosion, which will increase the incidence and progress of intergranular corrosion. Therefore, its dosage needs to be strictly controlled.
[0051] Furthermore, the present invention further fills the gaps between the crystal grains on the surface of the magnet by filling phase magnetic powder. During the pressing process, the filling phase magnetic powder effectively regulates the phase distribution, reduces the local aggregation of impurity elements inside the magnet, reduces the magnetic anisotropy of the magnet, and thus improves the overall magnetic properties of the magnet. At the same time, during the sintering and diffusion process, the main phase B element is compensated to a certain extent, which is beneficial to improving the density of the magnet. However, the amount of filling phase magnetic powder should not be too high. To a certain extent, low B content is beneficial to improving the orientation degree of the magnet, thereby improving the remanence of the magnet; at the same time, the content of neodymium-rich phase in the magnet is increased, and the magnetic exchange coupling effect is suppressed, thereby improving the coercive force of the magnet. Auxiliary alloys and filling phase magnetic powders complement each other, otherwise it may cause the impurity elements to be enriched inside the magnet, or the grain growth of each magnetic phase is inconsistent, resulting in a significant reduction in the magnetic properties and thermal stability of the magnet. In summary, the present invention controls the thickness of the magnetic domains of each phase by controlling the addition amount of the auxiliary alloy, and ensures the magnetic properties of the magnet by controlling the composition and particle size of the auxiliary alloy.
[0052] In addition, the present invention also adopts different pressing methods for the system of the present invention. Because in the traditional pressing method, the pressing form of low temperature and high pressure is adopted, but for the technical solution of the present invention, it is found in the study that the rough blank formed after simple low temperature and high pressure compaction is actually unfavorable for the liquid phase infiltration and flow of the auxiliary alloy, which will limit its strengthening effect. Therefore, the present invention adopts a multi-stage composite form for pressing, and adopts low temperature and high pressure pressing of the front and rear sections respectively, and intersperses a short time of high temperature and medium pressure pressing in between, so that the auxiliary alloy can form a certain softening and diffusion and play a certain link bonding effect, thereby improving the strengthening effect of the auxiliary alloy on the magnet, and having a more excellent anti-composite corrosion effect, so that the prepared NdFeB magnet maintains a long-term good thermal stability in a high temperature and high humidity working environment. However, it should be noted that in order to avoid destroying the magnetic properties of the magnet, the high temperature and medium pressure pressing process needs to be completed quickly, and the longest pressing time should not exceed 90 s, otherwise it is very easy to lose a large magnetic property, and within the range of 60 s, its loss is usually limited, and it can still maintain a better magnetic property.
[0053] The beneficial effects of the present invention are:
[0054] The NdFeB magnet prepared by the invention has good thermal stability and grain boundary corrosion resistance, thus showing good composite corrosion resistance, and shows good magnetic properties without other rare earth element doping and strengthening. DETAILED DESCRIPTION
[0055] The present invention is further described in detail below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0056] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.
[0057] Unless otherwise specified, the main phase magnetic powder and the filling phase magnetic powder used in the embodiments and comparative examples of the present invention are prepared by the following process:
[0058] Main phase magnetic powder preparation process:
[0059] Neodymium, boron and iron are weighed and mixed evenly according to the ratio of Nd 27.3 wt%, B 1.1 wt% and the balance Fe, and vacuum smelted at 1600°C. After cooling the ingot, the ingot is crushed and ground to 400 mesh to obtain the main phase magnetic powder;
[0060] Filling phase magnetic powder preparation process:
[0061] Neodymium, iron and boron were weighed and mixed evenly in the ratio of Nd 13.8 at%, Fe 5.5 at% and the balance B, and vacuum smelted at 1600°C. After the ingot was cooled, it was crushed and ground to obtain 1000-mesh filling phase magnetic powder.
[0062] Unless otherwise specified, the auxiliary alloy powders used in the embodiments and comparative examples of the present invention are prepared by weighing the raw material components according to the atomic ratio of the components in each embodiment and comparative example, for example, iron, neodymium copper alloy, and copper are weighed and mixed evenly, and then vacuum smelted at 1600° C. The ingots are cooled and crushed to obtain auxiliary alloy powder of 100 mesh.
[0063] Example 1
[0064] A method for preparing a high temperature resistant NdFeB magnet, the method comprising:
[0065] 1) Weigh the main phase magnetic powder, auxiliary alloy powder and filling phase magnetic powder in a mass ratio of 1:0.05:0.06 and mix them evenly to obtain mixed magnetic powder, wherein the content of the auxiliary alloy powder is: Fe 25.0 at%, NdCu 11.0 at%, and the balance is Cu;
[0066] The mixed magnetic powder is uniformly filled in the mold, and the orientation is carried out at 1.5 T for 35 minutes. During the orientation process, a pressure of 5 MPa is applied. After the orientation is completed, the rough magnet is pressed to obtain a rough magnet.
[0067] The suppression is divided into the following sections:
[0068] The first stage of pressing: the pressing temperature is 95 °C, the pressing pressure is 235 MPa, and the pressing time is 20 min;
[0069] The second stage of pressing: the pressing temperature is 520 °C, the pressing pressure is 75 MPa, and the pressing time is 50 s;
[0070] The third stage of pressing: the pressing temperature is 90 °C, the pressing pressure is 130 MPa, and the pressing time is 15 min;
[0071] 2) The magnet blank is placed in a vacuum atmosphere and sintered at 1050 °C for 4 h, then the surface is cleaned, and then tempered at 650 °C for 2 h and 400 °C for 5 h to obtain a high-temperature resistant NdFeB magnet.
[0072] The high temperature resistant NdFeB magnets prepared in this example were subjected to saturation magnetization and then characterized. The characterization specifically included the remanence intensity (Br) and mass (m0) of the original sample at room temperature (20±1°C), the calculation of the remanence temperature coefficient (αBr) in each range starting from 25°C, and the calculation of the remanence temperature coefficient (αBr) in each range. T ), and the same characterization was performed on corrosion samples A and B. Corrosion samples A and B were placed in a coastal cooperative unit to simulate corrosion in a real environment, where:
[0073] Corrosion sample A was placed on an open constant temperature heating table (model: TW series thin layer constant temperature heating plate), heated to 90 °C and exposed to air for 21 days. The sea level of corrosion sample A was about 1 m (chlorine-rich area), and the maximum distance from the coast was about 55 m.
[0074] Corrosion sample B was placed on an open constant temperature heating table (model: TW series thin layer constant temperature heating plate), heated to 90 °C and exposed to air for 21 days. The sea level of corrosion sample A was about 30 m (chlorine-poor area), and the maximum distance from the coast was about 55 m.
[0075] After completing the simulated corrosion in the real environment, the corroded samples A and B were retrieved and subjected to the same characterization as the original samples, where the mass characterization results were used to calculate the mass loss rate (△m).
[0076] The characterization results are shown in Table 1 below.
[0077] Table 1: Performance characterization of high temperature resistant NdFeB magnets after saturation magnetization in Example 1
[0078]
[0079] According to the results in Table 1, the residual temperature coefficient (αBr T ) It can be clearly seen that the NdFeB magnet of the present invention has good thermal stability, which is generally better than the remanence temperature coefficient of -0.12% / ℃ to -0.08% / ℃ exhibited by conventional sintered NdFeB magnets, and exhibits good initial magnetic properties and heat resistance stability.
[0080] By comparing the corrosion sample A and the corrosion sample B, it can be clearly seen that the corrosion sample A and the corrosion sample B have been subjected to different realistic environment simulation corrosion. In previous studies, it is often believed that the corrosion conditions of the corrosion sample A and the corrosion sample B are the same, while ignoring the influence of actual environmental factors and seasonal factors, changing the distribution of environmental chloride ions, but not significantly changing the trend of heat resistance of NdFeB magnets. According to the characterization results in the above table, the remanent magnetic strength of the corrosion sample A and the corrosion sample B has not changed significantly, but there is still a certain gap, because the corrosion forms of the two are different, the corrosion sample B mainly presents a thermal-grain boundary composite corrosion mechanism, and the corrosion sample A has a certain salt spray corrosion on this basis, and the mass change rate has a very significant difference. Because salt spray corrosion shows a stronger macroscopic physical destructive effect on the magnet, it also has a certain direct impact on the remanent magnetic strength. This is also one of the reasons why salt spray corrosion can often cover up the grain boundary corrosion that occurs at the same time. Of course, it is also because the technical solution of the present invention does not specifically strengthen the resistance of the magnet to salt spray corrosion, but from the subsequent remanent magnetic temperature coefficient (αBr T ) From the characterization results, it can be clearly seen that the effect of salt spray corrosion on the residual magnetism temperature coefficient is relatively limited, because compared with the corrosion sample B, the corrosion sample A has more obvious salt spray corrosion, but the change range of the residual magnetism temperature coefficient of the corrosion sample A is relatively close to that of the corrosion sample B, and both have decreased relative to the initial sample, but the decrease is relatively small. It can also be seen that the high-temperature resistant NdFeB magnet of the present invention has a good anti-granular corrosion effect. By inhibiting the grain boundary corrosion in the composite corrosion mechanism and ensuring that the magnet has good high-temperature resistance, the high-temperature resistant NdFeB magnet of the present invention can show good and stable high-temperature resistance in offshore or coastal environments, and is suitable for use in motors. At the same time, in view of its weak resistance to salt spray corrosion, conventional means such as salt spray protective coatings can be appropriately used to strengthen it to a certain extent. Based on the current research and development progress, it has not yet been able to effectively achieve multiple enhancements of resistance to salt spray corrosion and resistance to grain boundary corrosion.
[0081] Example 2
[0082] A method for preparing a high temperature resistant NdFeB magnet, the method comprising:
[0083] 1) Weigh the main phase magnetic powder, auxiliary alloy powder and filling phase magnetic powder in a mass ratio of 1:0.05:0.06 and mix them evenly to obtain mixed magnetic powder, wherein the content of the auxiliary alloy powder is: Fe25.0 at%, NdCu 14.5 at%, and the balance is Cu;
[0084] The mixed magnetic powder is uniformly filled in the mold, and the orientation is carried out at 1.5 T for 35 minutes. During the orientation process, a pressure of 5 MPa is applied. After the orientation is completed, the rough magnet is pressed to obtain a rough magnet.
[0085] The suppression is divided into the following sections:
[0086] The first stage of pressing: the pressing temperature is 95 °C, the pressing pressure is 235 MPa, and the pressing time is 20 min;
[0087] The second stage of pressing: the pressing temperature is 520 °C, the pressing pressure is 75 MPa, and the pressing time is 50 s;
[0088] The third stage of pressing: the pressing temperature is 90 °C, the pressing pressure is 130 MPa, and the pressing time is 15 min;
[0089] 2) The magnet blank is placed in a vacuum atmosphere and sintered at 1050 °C for 4 h, then the surface is cleaned, and then tempered at 650 °C for 2 h and 400 °C for 5 h to obtain a high-temperature resistant NdFeB magnet.
[0090] The high temperature resistant NdFeB magnet prepared in this example was subjected to saturation magnetization and then subjected to performance characterization. The performance characterization method was the same as that in Example 1, and the characterization results of this example are shown in Table 2 below.
[0091] Table 2: Performance characterization of high temperature resistant NdFeB magnets after saturation magnetization in Example 2
[0092]
[0093] Based on the characterization results in Table 2 above, it can be seen that the NdFeB magnet prepared in this example also has good resistance to combined corrosion of intergranular corrosion and thermal corrosion, showing good heat resistance and the heat resistance does not decrease significantly under the action of combined corrosion.
[0094] Example 3
[0095] A method for preparing a high temperature resistant NdFeB magnet, the method comprising:
[0096] 1) Weigh the main phase magnetic powder, auxiliary alloy powder and filling phase magnetic powder in a mass ratio of 1:0.05:0.06 and mix them evenly to obtain mixed magnetic powder, wherein the content of the auxiliary alloy powder is: Fe 25.0 at%, NdCu 18.0 at%, and the balance is Cu;
[0097] The mixed magnetic powder is uniformly filled in the mold, and the orientation is carried out at 1.5 T for 35 minutes. During the orientation process, a pressure of 5 MPa is applied. After the orientation is completed, the rough magnet is pressed to obtain a rough magnet.
[0098] The suppression is divided into the following sections:
[0099] The first stage of pressing: the pressing temperature is 95 °C, the pressing pressure is 235 MPa, and the pressing time is 20 min;
[0100] The second stage of pressing: the pressing temperature is 520 °C, the pressing pressure is 75 MPa, and the pressing time is 50 s;
[0101] The third stage of pressing: the pressing temperature is 90 °C, the pressing pressure is 130 MPa, and the pressing time is 15 min;
[0102] 2) The magnet blank is placed in a vacuum atmosphere and sintered at 1050 °C for 4 h, then the surface is cleaned, and then tempered at 650 °C for 2 h and 400 °C for 5 h to obtain a high-temperature resistant NdFeB magnet.
[0103] The high temperature resistant NdFeB magnet prepared in this example was subjected to saturation magnetization and then its performance was characterized. The performance characterization method was the same as that in Example 1, and the characterization results of this example are shown in Table 3 below.
[0104] Table 3: Performance characterization of high temperature resistant NdFeB magnets after saturation magnetization in Example 3
[0105]
[0106] Combined with the data in Table 3 and the characterization results of Examples 1 to 2, it can be seen that when the other preparation parameters and conditions are inconvenient, the amount of NdCu alloy in the auxiliary alloy powder used in the present invention gradually increases, and the actual composite corrosion resistance shows a trend of first rising and then falling. On the one hand, as mentioned above, the increase in the actual rare earth content and type will actually lead to the weakening of the composite corrosion resistance of the NdFeB magnet, thereby showing poor high temperature resistance. As for the component content of the NdCu alloy in the auxiliary alloy, it also has a certain impact on the role of the auxiliary alloy powder to a certain extent. Because the main function of the auxiliary alloy powder is to infiltrate the link and inhibit the occurrence of intergranular corrosion by forming a thin layer of continuous grain boundary phase, when the Nd content in the auxiliary alloy powder increases within a reasonable range, it is conducive to the occurrence of this process, but similarly, when the continuous grain boundary phase continues to increase, it will actually participate in the grain boundary corrosion process, but increase the probability of grain boundary corrosion, thus leading to a decrease in high temperature resistance under the action of composite corrosion.
[0107] Comparative Example 1
[0108] A method for preparing a high temperature resistant NdFeB magnet, the method comprising:
[0109] 1) Weigh the main phase magnetic powder, auxiliary alloy powder, filling phase magnetic powder and metal dysprosium powder in a mass ratio of 1:0.05:0.06:0.02 and mix them evenly to obtain mixed magnetic powder, wherein the content of the auxiliary alloy powder is: Fe 25.0 at%, NdCu 14.5 at%, and the balance is Cu;
[0110] The mixed magnetic powder is uniformly filled in the mold, and the orientation is carried out at 1.5 T for 35 minutes. During the orientation process, a pressure of 5 MPa is applied. After the orientation is completed, the rough magnet is pressed to obtain a rough magnet.
[0111] The suppression is divided into the following sections:
[0112] The first stage of pressing: the pressing temperature is 95 °C, the pressing pressure is 235 MPa, and the pressing time is 20 min;
[0113] The second stage of pressing: the pressing temperature is 520 °C, the pressing pressure is 75 MPa, and the pressing time is 50 s;
[0114] The third stage of pressing: the pressing temperature is 90 °C, the pressing pressure is 130 MPa, and the pressing time is 15 min;
[0115] 2) The magnet blank is placed in a vacuum atmosphere and sintered at 1050 °C for 4 h, then the surface is cleaned, and then tempered at 650 °C for 2 h and 400 °C for 5 h to obtain a high-temperature resistant NdFeB magnet.
[0116] The high temperature resistant NdFeB magnet prepared in this example was subjected to saturation magnetization and then subjected to performance characterization. The performance characterization method was the same as that in Example 1, and the characterization results of this example are shown in Table 4 below.
[0117] Table 4: Performance characterization of high temperature resistant NdFeB magnet after saturation magnetization in Comparative Example 1
[0118]
[0119] From the data in Table 4 above, it can be seen that as a common NdFeB strengthening element, the addition of Dy is indeed beneficial to the magnetic properties of NdFeB magnets under mild conditions, and its remanent magnetic strength and high temperature resistance are enhanced to a certain extent. However, from the corrosion samples A and B in this example, it can be clearly seen that the heating of Dy has instead seriously damaged the ability of NdFeB magnets to resist grain boundary-thermal composite corrosion, because the heating of Dy changes the structure and composition of the crystals and grain boundaries, forming more rare earth-rich phase components that are prone to grain boundary corrosion. For example, the common diffusion form of Dy will form a heavy rare earth-rich area, resulting in changes in the chemical composition of the grain boundary area, changes in the distribution density and structure of the grain boundary, and increases the electrochemical activity difference between the phase components. Similarly, as a common Tb element doping used to strengthen NdFeB magnets, it is doped with a mass ratio of 1.8 wt% of the main phase. The experimental results also show that its magnetic properties under mild conditions are enhanced, which is in line with expectations, but the same corrosion sample B shows a large performance degradation, and its remanent magnetization temperature coefficient αBr in the temperature range of 25-120 ℃ T It is only -0.096% / ℃. Therefore, it is actually difficult to maintain good high temperature resistance.
[0120] Comparative Example 2
[0121] A method for preparing a high temperature resistant NdFeB magnet, the method comprising:
[0122] 1) Weigh the main phase magnetic powder, auxiliary alloy powder and filling phase magnetic powder in a mass ratio of 1:0.05:0.06 and mix them evenly to obtain mixed magnetic powder, wherein the content of the auxiliary alloy powder is: Fe 25.0 at%, NdCu 14.5 at%, and the balance is Cu;
[0123] The mixed magnetic powder is uniformly filled in the mold, and the orientation is carried out at 1.5 T for 35 minutes. During the orientation process, a pressure of 5 MPa is applied. After the orientation is completed, the rough magnet is pressed to obtain a rough magnet.
[0124] The suppression is divided into the following sections:
[0125] The first stage of pressing: the pressing temperature is 95 °C, the pressing pressure is 235 MPa, and the pressing time is 21 min;
[0126] The second stage of pressing: the pressing temperature is 90 °C, the pressing pressure is 130 MPa, and the pressing time is 15 min;
[0127] 2) The magnet blank is placed in a vacuum atmosphere and sintered at 1050 °C for 4 h, then the surface is cleaned, and then tempered at 650 °C for 2 h and 400 °C for 5 h to obtain a high-temperature resistant NdFeB magnet.
[0128] The high temperature resistant NdFeB magnet prepared in this example was subjected to saturation magnetization and then subjected to performance characterization. The performance characterization method was the same as that in Example 1, and the characterization results of this example are shown in Table 5 below.
[0129] Table 5: Performance characterization of high temperature resistant NdFeB magnets after saturation magnetization in Comparative Example 2
[0130]
[0131] From the characterization results in Table 5 above, short-term high-temperature pressing is not used in the preparation process of the NdFeB magnet in this example, which has no significant effect on the performance of the magnet. However, it can be clearly seen from the comparison between the corrosion sample A and the corrosion sample B and the original sample that short-term high-temperature pressing has a significant impact on the ability of the NdFeB magnet to resist composite corrosion by strengthening the auxiliary alloy powder. In the absence of high-temperature pressing, the density of the magnet is limited, and the auxiliary alloy powder is difficult to play a strong and effective role in infiltration and linking, and the growth and distribution of the thin layer of continuous grain boundary phase are affected, resulting in a decrease in performance, and it can also be clearly seen that its resistance to salt spray corrosion is also greatly weakened. But in the same way, we also know that the high-temperature pressing process is very likely to cause a permanent and irreversible decrease in the magnetic properties of the NdFeB magnet, because the present invention needs to strictly control the pressing time to ensure the effective coordination of magnetic properties and corrosion resistance.
[0132] Comparative Example 3
[0133] A method for preparing a high temperature resistant NdFeB magnet, the method comprising:
[0134] 1) Weigh the main phase magnetic powder, auxiliary alloy powder and filling phase magnetic powder in a mass ratio of 1:0.05:0.08 and mix them evenly to obtain mixed magnetic powder, wherein the content of the auxiliary alloy powder is: Fe 25.0 at%, NdCu 14.5 at%, and the balance is Cu;
[0135] The mixed magnetic powder is uniformly filled in the mold, and the orientation is carried out at 1.5 T for 35 minutes. During the orientation process, a pressure of 5 MPa is applied. After the orientation is completed, the rough magnet is pressed to obtain a rough magnet.
[0136] The suppression is divided into the following sections:
[0137] The first stage of pressing: the pressing temperature is 95 °C, the pressing pressure is 235 MPa, and the pressing time is 20 min;
[0138] The second stage of pressing: the pressing temperature is 520 °C, the pressing pressure is 75 MPa, and the pressing time is 50 s;
[0139] The third stage of pressing: the pressing temperature is 90 °C, the pressing pressure is 130 MPa, and the pressing time is 15 min;
[0140] 2) The magnet blank is placed in a vacuum atmosphere and sintered at 1050 °C for 4 h, then the surface is cleaned, and then tempered at 650 °C for 2 h and 400 °C for 5 h to obtain a high-temperature resistant NdFeB magnet.
[0141] The high temperature resistant NdFeB magnet prepared in this example was subjected to saturation magnetization and then subjected to performance characterization. The performance characterization method was the same as that in Example 1, and the characterization results of this example are shown in Table 6 below.
[0142] Table 6: Performance characterization of high temperature resistant NdFeB magnets after saturation magnetization in Comparative Example 3
[0143]
[0144] Based on the characterization results in Table 6 above, too much filling phase magnetic powder was added during the preparation process of this example, so the B element content was higher, which was not conducive to the orientation of the magnet, resulting in the inability to effectively maintain the remanence of the magnet. At the same time, the formation of the neodymium-rich phase in the magnet was reduced, resulting in obvious short-range exchange coupling between the grains, resulting in low coercivity. In multiple tests with filling phase magnetic powder as a variable, it was shown that the optimal addition amount of filling phase magnetic powder should be 4-6 wt% of the main phase magnetic powder.
Claims
1. A method for preparing a high temperature resistant neodymium iron boron magnet, characterized in that: The method comprises: 1) respectively preparing main phase magnetic powder, auxiliary alloy powder and filling phase magnetic powder, mixing them evenly to obtain mixed magnetic powder, evenly filling the mixed magnetic powder in a mold, orienting and pressing to obtain a magnet blank; 2) Sintering the magnet blank, cleaning the surface and tempering to obtain a high temperature resistant NdFeB magnet; Step 1) The main phase magnetic powder is composed of: Nd 27.0~28.0 wt%, B 1.0~1.2 wt%, the balance is Fe; Step 1) The auxiliary alloy powder is composed of: Fe 25.0~27.0 at%, NdCu 11.0~18.0 at%, the balance is Cu; Step 1) The filling phase magnetic powder is composed of: Nd 13.8~14.5 at%, Fe 5.5~6.5 at%, the balance is B; Step 1) The pressing is performed in stages, and the staged pressing includes a first stage pressing procedure, a second stage pressing procedure and a third stage pressing procedure in sequence, and all the pressing procedures are in the form of isostatic pressing; The first-stage pressing procedure controls the pressing temperature to be 80-100°C, the pressing pressure to be 220-250 MPa, and the pressing time to be 15-25 min; The two-stage pressing program controls the pressing temperature to be 510-530°C, the pressing pressure to be 60-80 MPa, and the pressing time to be 30-60 s; The three-stage pressing program controls the pressing temperature to be 70-110°C, the pressing pressure to be 120-130 MPa, and the pressing time to be 10-20 min; In step 1), the mass ratio of the main phase magnetic powder, the auxiliary alloy powder and the filling phase magnetic powder is 1: (0.03-0.08): (0.04-0.06).
2. The method for preparing a high temperature resistant NdFeB magnet according to claim 1, characterized in that: Step 1) The main phase magnetic powder is respectively made of neodymium, boron and iron according to the composition, mixed evenly, smelted in an inert gas and then crushed to 400-500 mesh to obtain the main phase magnetic powder; Step 1) The auxiliary alloy powder is respectively made of iron, neodymium copper alloy and copper, and mixed evenly, smelted in an inert gas, and then crushed into auxiliary alloy powder of 100-200 mesh; Step 1) The filling phase magnetic powder is prepared by mixing neodymium, boron and iron according to the composition, smelting them in an inert gas and then crushing them into 1000-1200 meshes to obtain the filling phase magnetic powder.
3. The method for preparing a high temperature resistant NdFeB magnet according to claim 1, characterized in that: In step 1), the orientation magnetic field intensity is controlled to be 1.5 to 1.7 T, the orientation time is 25 to 35 min, and a pressing pressure of 4 to 6 MPa is applied during the orientation process.
4. The method for preparing a high temperature resistant NdFeB magnet according to claim 1, characterized in that: Step 2) The sintering is carried out in a protective atmosphere at a sintering temperature of 1050-1080° C. and a sintering time of 3-4 hours.
5. The method for preparing a high temperature resistant NdFeB magnet according to claim 1, characterized in that: Step 2) the tempering is staged tempering; The staged tempering includes, in sequence, maintaining the temperature at 550-650°C for 2.0-2.5 h, and maintaining the temperature at 400-500°C for 4.5-5.0 h.
6. A high temperature resistant NdFeB magnet obtained by the method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Method of preparing superhard alloy bar by using WC-Co composite powder as raw material through dry bag isostatic pressing and low-pressure sintering
CN108145158A
Vehicle-mounted high-temperature-resistant neodymium iron boron permanent magnet and preparation method thereof
CN116825462A